Perforated Kirschner wire tension band in the treatment of Mayo IIA olecranon fractures - Yu, Xiang; Li, Qi; Li, Yu-Zhi; Lu, Hai-Jian; Ao, Rong-Guang; Liu, Bing-Li (Frontiers in Surgery, 2024)
PurposeTo explore the clinical efficacy of perforated Kirschner wire tension band in the treatment of Mayo IIA olecranon fracture.MethodA retrospective study was conducted to analyze the clinical data of 96 adult patients with olecranon fractures of the ulna. Thirty-four cases underwent perforated Kirschner wire tension band fixation(group A), which included 21 males and 13 females, with an average age of 49.1 ± 11.57 years. Thirty-two cases received fixation with an olecranon anatomical plate (group B), comprising 19 males and 13 females, with an average age of 48.9 ± 8.84 years. Additionally, 30 cases were treated with ordinary Kirschner wire tension band fixation (group C), consisting of 18 males and 12 females, with an average age of 46.6 ± 12.03 years. The study compared various outcomes among the three groups, including operation time, intraoperative blood loss, number of fluoroscopy exposures, postoperative visual analogue score (VAS), fracture healing time, internal fixation failure rates, skin irritation rates, and the Broberg-Morrey score for elbow joint function at the final follow-up.ResultAll patients were followed for a duration of 15 to 21 months, with an average follow-up period of 18 months. The operation time, intraoperative blood loss, number of fluoroscopy sessions, fracture healing time, and incidence of skin irritation for group A were recorded as (73.8 ± 11.72) min, (113.5 ± 20.73) milliliters, (7.5 ± 1.96) times, and (3.7 ± 1.46) months, respectively, with 1 case of skin irritation. In group B, the corresponding values were (98.4 ± 10.46) min, (154.7 ± 20.11) milliliters, (11.8 ± 2.78) times, and (4.3 ± 1.69) months, with 5 cases of skin irritation. For group C, the values were (81.7 ± 15.66) min, (115.5 ± 18.82) milliliters, (7.3 ± 1.99) times, and (4.3 ± 1.86) months, with 7 cases of skin irritation. Group A demonstrated superior outcomes compared to group B in terms of intraoperative blood loss and number of fluoroscopy sessions, and outperformed both group B and group C regarding operation time, fracture healing time, and skin irritation. These differences were statistically significant (P < 0.05).ConclusionPerforated Kirschner wire Tension band is an effective method for treating olecranon fractures. This technique is associated with a short operative time, minimal intraoperative blood loss, and a reduced need for fluoroscopy. Additionally, it promotes fracture healing and significantly reduces the risk of complications, such as postoperative skin irritation.